The livelihood assessment tool-kit : (Food and agriculture Organization of the United nations (FAO),International labor organization (ILO), 2009)
Assessing the impact of disasters on the livelihoods of people and the capacity and opportunities for recovery and increased resilience to future events is an important part of the response to disasters, yet current assessment systems are often weak, uncoordinated and are not strongly linked to livelihood recovery interventons. In oder to improve understanding of the impact of disacters on livelihoods, the Food and agriculture Organization of the United nations (FAO) and International labor organization (ILO) have jointly developed the Livelihood Assessment Tool - kit (LAT).